Positive Mental Health Promotion - interventions developed through informatics applications: a scoping review (RevSALUS - Revista Científica Internacional da Rede Académica das Ciências da Saúde da Lusofonia, 2025)
Introduction: A review was conducted on the effectiveness of positive mental health promotion interventions using computer applications via a webpage and a smartphone. Objective: Map the existing evidence on interventions for the promotion of positive mental health (PMH) using web-based and mobile phone applications and identify the characteristics and contexts of these interventions in adult participants. Material and methods: The review was implemented according to the Joanna Briggs Institute guidelines. No time limit was established for the studies to be addressed in the review and participants had to be eighteen years old or older. The results of the final search are presented using a Preferred Reporting Items for Systematic Reviews and Meta-analyses diagram. For writing this scoping review, the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews Checklist were used. Results: Nine studies were included. Several computer applications were identified, including their characteristics, participants (over eighteen years of age), and various contexts of implementation. The interventions have been developed with students, nurses and other health professionals, teachers, and informal caregivers of chronically ill patients, using a computer application on a webpage or smartphone using a variety of activities and audiovisual media. The programs ranged in length from fourteen days to eighty-seven weeks, with sessions varying from one to forty-four, lasting from one minute to one hundred and fifty minutes each. Conclusion: PMH promotion interventions using computer applications can be developed via webpage and smartphone, employing a variety of activities through interactive media.